Religiosity: Protective or Risk Factor for Posttraumatic Distress Among Adolescents Who Were Exposed to Different Types of Acts of Political Violence - Sakat, Efrat (Journal of interpersonal violence, 2021)
This study examined the potential moderating effects of religiosity on the associations between exposure to acts of political violence and posttraumatic stress symptoms (PTS) among Jewish adolescents in Israel. In addition, it examined whether self-reported physical and interpersonal exposure to acts of political violence predicts PTS symptoms beyond the objective exposure effects (i.e., the proximity of participants’ place of residence to high-, moderate-, or low-intensity political violence). A representative sample of 2,992 Jewish high school students (Grades 10 and 11) was taken. We used self-reporting to measure the level of religiosity and the Impact of Events Scale–Revised (IES-R) to measure PTS symptoms. Results show that self-reported exposure to acts of political violence adds a significant additional amount of variance to the prediction of PTS symptoms after objective exposure is already included in the regression equation. Religiosity was found as a risk factor for PTS symptoms such that the greater the religiosity of the adolescents, the higher their PTS symptoms. Therefore, prevention interventions should target the vulnerable group of religious Jewish adolescents.